P063 Consensus-based recommendations for treat to target management of immunoglobulin A vasculitis. (11th November 2021) - Abu-Zaid, M H; Tabra, S A; Salah, S; Lotfy, H; Abdulhady, H; Salah, H; El Gaafary, M; Farag, Y; Eissa, M; Maher, S Esam; Radwan, A; El-Shanawany, Amira T; et al.
Abstract: Background: IgAvasculitis (IgAV) is the commonest cause of vasculitis in childhood. It is characterized by small vessel vasculitis of the skin, gastrointestinal tract, kidneys, joints, and, rarely, the lungs and the central nervous system. There is paucity of international guidelines for management of IgA V. the Objective is to develop guidelines specific for Egyptian children with IgA vasculitis. Method: This study was carried out to achieve an Egyptian expert consensus on a treat-to-target management strategy for IgA vasculitis using Delphi technique. The preliminary scientific committee identified a total of 16 key clinical questions according to the Patient/Population, Intervention, Comparison, and Outcomes (PICO) approach. Delphi process was implemented (2-rounds) to reach a consensus. Results: An online questionnaire were sent to expert panel ( n = 26) who participated in the two rounds. At the end of round 2, a total of 20 recommendation items, categorized into 2 sections were obtained. Agreement with the recommendations (rank 7–9) ranged from 91.7–100%. Consensus was reached (i.e. ≥75% of respondents strongly agreed or agreed) on the wording of all the 20 clinical standards identified by the scientific committee. Algorithms for the management have been suggested. Conclusion: This was an expert, consensus recommendations for the diagnosis and treatment of IgA V and IgA V nephritis, based on best available evidence and expert opinion.